Evaluating Actual Credibility Criteria of Internet-based Scientific Information of Adult Learners - Angela C Bliss (Adult Education Research Conference, 2016)
Self-directed adult learners access and evaluate scientific information on the Internet. This paper will discuss methodologies proposed to identify credibility criteria employed during these online learning endeavors.
Keywords: Self-directed learners; online; credibility criteria; science